2013
DOI: 10.1111/joor.12111
|View full text |Cite
|
Sign up to set email alerts
|

Changes in masticatory function after injection of botulinum toxin type A to masticatory muscles

Abstract: This study examined changes in masticatory function after botulinum toxin type A (BTX-A) injection using objective and subjective tests during 12 weeks. Also, we compared differences in masticatory function between group in which only masseter muscle (M group) was injected and group in which masseter and temporal muscle (M-T group) were injected. Forty subjects were assigned into two groups; M group (n = 20) and the M-T group (n = 20). The Meditoxin(®) was used as BTX-A injection. The mixing ability index (MAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
3
12
0
1
Order By: Relevance
“…These results support a dose-duration effect for the toxin [ 25 ]. In addition, MP which is partially related to muscle activity was reduced after 7 to 28 days of BoNT-A injections, corroborating another study [ 26 ] reporting the improvement of MP following BoNT-A applications after 28 days and a completed returned to baseline values after 90 days. Conversely BoNTA-L compared to SS showed no significant differences at any evaluation point.…”
Section: Discussionsupporting
confidence: 88%
“…These results support a dose-duration effect for the toxin [ 25 ]. In addition, MP which is partially related to muscle activity was reduced after 7 to 28 days of BoNT-A injections, corroborating another study [ 26 ] reporting the improvement of MP following BoNT-A applications after 28 days and a completed returned to baseline values after 90 days. Conversely BoNTA-L compared to SS showed no significant differences at any evaluation point.…”
Section: Discussionsupporting
confidence: 88%
“…According to Ahn et al and Kim et al, patients experienced a 20‐40 percent decrease in mean bite force 2 weeks after treatment compared to pre‐injection values. According to Park et al, when compared to pre‐injection values at 4 weeks post‐injection, masticatory function decreased by 89.2% (mixing ability index), 12.2% (food intake ability), and 32.2% (visual analog scale), respectively. The bite force will gradually be restored in 3‐8 weeks and usually returns to pre‐injection levels in around 12 weeks .…”
Section: Resultsmentioning
confidence: 99%
“…According to Park et al, when compared to pre‐injection values at 4 weeks post‐injection, masticatory function decreased by 89.2% (mixing ability index), 12.2% (food intake ability), and 32.2% (visual analog scale), respectively. The bite force will gradually be restored in 3‐8 weeks and usually returns to pre‐injection levels in around 12 weeks . In a MRI evaluation study, muscular atrophy persisted for 4 months after a single treatment and full recovery took sixth months …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, Sato et al [ 2 ] proposed the use of artificial food composed of two-color utility wax cubes and formulated a mixing ability index (MAI), scores of which are determined by the degree of color-mixing and the shape of the wax after chewing. Several previous studies have reported that the FIA and MAI scores can successfully evaluate masticatory function in patients with temporomandibular disorders or botulinum toxin injections and in orthodontic patients [ 3 4 5 ].…”
Section: Introductionmentioning
confidence: 99%